Phytoremediation of landfill leachate using hibiscus cannabinus and acacia mangium / Meera a/p Munusamy - Munusamy, Meera (2013)
Resource managers are challenged with waste disposal, leachate produced from its degradation and its impacts to the environment. Jeram landfill leachate contains high amount of Fe, As, CN and NH3-N. Knowledge about the response of Hibiscus cannabinus (Kenaf) and Acacia mangium (Akasia) to landfill leachate irrigation is limited; therefore this study was initiated to investigate the effect of phytoremediation on Jeram landfill leachate. During pot-culture research, Kenaf and Akasia were irrigated for a period of 120 days in a nursery. Also, hydroponic culture employing Kenaf and Akasia for uptake of pollutants from leachate was carried out in a constructed wetland for contaminant bioconcentration study. These results detail the extensive variation in treatments of leachate, plant responses to leachate irrigation, along with the need and efficacy of plant and growth medium selection to choose superior phytoremediator plant. Leachate which was pretreated with FeCl3 (4g/L) recorded an optimum condition for highest phytoremediation rate at 25% (0.24% N-content) in Kenaf and Akasia in both the potculture and hydroponic-culture systems. Evaluation consisted of testing for differences in plant growth and biomass of leaves, stems, and roots, along with total Fe, As, CN and NH3-N concentration in control and harvest soil, wastewater and in leaf, stems and root tissue. Accumulation of Fe, As, CN and NH3-N was assessed based on mathematical models: Bioconcentration Factor (BCF), Translocation Factor (TF) and Bioaccumulation Kinetics. Kenaf sequestered 0.1–0.7 mg As, 18.5-51.7 mg Fe, 0.1-0.6 mg CN and 2.4-10.5mg NH3-N /g dry weight, which implies that Kenaf can be a bioavailable sink for toxic metals. Akasia, being a leguminous plant recorded higher BCF than Kenaf for Fe (9.1-14.3), NH3-N (4.2-8.8), CN (1.1-4.3) and As (1.5-2.9). In hydroponic culture, Akasia marked a iv 24% increase in contaminant uptake efficiency compared to Kenaf through rhizofiltration mechanism. The ability of Kenaf and Akasia to tolerate these metals and avoid phytotoxicity could be attributed to the phytostabilisation of the metals in the plant roots and hence reduction of toxic metal mobility (translocation factor < 1). During irrigation with leachate, Kenaf and Akasia were also found to have higher biomass compared to control plants. Kenaf and Akasia recorded 49% and 53% higher bioaccumulation capacity, respectively indicating its suitability for phytoextraction of leachate contaminated sites. The bioaccumulation rate constant of the contaminants in Kenaf and Akasia were in the range of 0.01-0.03 and 0.02–0.04/day, respectively. Half-life of contaminants in Kenaf and Akasia were 35-60 and 25-68 days, respectively. Development of e-Phytoremediation Modeling System (e-PMS) marked an integration of biological and artificial intelligence knowledge, thus serves as Decision Support System (DSS) platform for future research directions in phytoremediation. The user-friendly interphase and models applied determines the potential and performance of phytoremediator plants. Overall, these results documented successful uptake of nutrients without detrimental impacts to plant health, which validated the use of landfill leachate as an irrigation and fertilization source for Kenaf and Akasia. In addition, these data will serve as a basis for researchers and resource managers making decisions about future leachate remediation projects.